CARBONATES FROM THE LOWER PART OF TRANSITION ZONE OR EVEN THE LOWER MANTLE - Brenker F.E.; Szymanski A.; Joswig W.; Vollmer C.; Vincze L.; Vekemans B.; Janssens K.; Szaloki I.; Nasdala L.; Kaminsky F. (My University, 2007)
Effective CO2-storage in the shallow solid Earth mainly occurs by the formation of carbonates. Although the possibility of transport and storage of carbonates to great depth is demonstrated experimentally, ultra-deep mantle carbonates have not been found before. Applying several in situ analytical techniques on inclusions in diamonds from Juina (Brazil) originating from the lower part of the transition zone (> 580 km) or even the lower mantle (> 670 km), reveal the existence of deep Earth carbonates. These finding unquestionably show that at least locally carbonates exist within the deep Earth and may indicate that the Earth's global CO2-cycle has an ultra-deep extension. © 2007 Elsevier B.V. All rights reserved.
Keywords: INCLUSIONS IN DIAMOND; JUINA; MANTLE HETEROGENEITY; RAMAN SPECTROSCOPY; X-RAY FLUORESCENCE